ANALISIS TEKNO EKONOMI BRIKET ARANG DARI SAMPAH DAUN KERING - Meylinda Mulyati (Teknoin, 2016)
Nowadays, Energy comsumption in the world tend to depend on fossil fuels. Alternative energy is still less developed. Indonesia has potential to develop alternative energy, especially biomass. One of this biomass is dried leaf that can be done to be briquettes. Dried leaf briquettes can be as an alternative fuel may be a solution for energy crisis. Economically that briquetting of the dried leaf could be a very promising business. Briquetting of dry leaf can be done with the simplest of techniques. Itâ€™s necessary doing techno economic analysis of charcoal briquettes of dried leaf. This research was done by using two types of adhesives briquettes Â namely tapioca flour and sago with a weight percentage of 30% by weight of dry leaf briquette. The result of this research is the best briquette adhesive is tapioca flour because it produces water content of 25%, ash content of 13.85%, carbon content 61.15% and calorific value is 7100.23 calories. If this compare with adhesive sago are the water content is 23.08%, ash content of 10.5%, carbon content 69.41% and calorific value is 6325.66 calories. When compared with the comparative quality of briquettes SNI no.1 / 6235/200, only the carbon content of which has not reached for both types of the adhesive. The results of the calculation of the cost of production, to produce briquettes with a capacity of 15,000 kg of briquettes per year is Rp 42,312,600.00 while the cost of production Rp 2820.00/kg and selling price that can be offered to consumers are Rp 4,300/Kg. In this economic calculation values obtained BEP (kg) is 15008.75 kg and BEP in rupiah at Rp 42,324,675.00. While its payback period is for 90 days.